Species of (Code) spaces - Papadimitraki, Pinelopi (2017)
As digital technologies make a powerful impact on the production of space and software mediates most of our everyday activities, we find ourselves living, working and interacting in the common ground of code and space. The environmental diffusion of computing should be considered in relation to the increasing acceleration and simultaneity of socio-spatial and economic processes, characteristic conditions of a dynamic spatial ontology that evolved during the past decades, changing the ways we inhabit, design and think about our environments. By following the gradual hybridization of space and time, this essay investigates the ways in which software and communication networks infuse space with temporal qualities, enhancing its inherent mediality with successive layers of meaning. An account of this in urban scale is the endeavour of smart cities, a fluid field of tension and negotiation between centralized managerial visions and bottom-up participation and appropriation initiatives. Finally, as spatial production becomes increasingly transdisciplinary and the digital turn reaches a certain level of maturity, the role of the architect and the architectural object changes drastically. Cedric Price famously argued that the best solution to a spatial problem is not necessarily a building, but the question is still pending – could it then be code?